2018
DOI: 10.1080/02648725.2018.1474320
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdoviruses as vaccine platforms for infectious disease and cancer

Abstract: The family Rhabdoviridae (RV) comprises a large, genetically diverse collection of single-stranded, negative sense RNA viruses from the order Mononegavirales. Several RV members are being developed as live-attenuated vaccine vectors for the prevention or treatment of infectious disease and cancer. These include the prototype recombinant Vesicular Stomatitis Virus (rVSV) and the more recently developed recombinant Maraba Virus, both species within the genus Vesiculoviridae. A relatively strong safety profile in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“…For example, genetically simple and pro-inflammatory viruses, such as rhabdoviruses, are suitable for cancer vaccine combinations due to the rapid dissemination of such viruses in secondary lymphoid organ and the TME. Conversely, more complex and slower-replicating viruses, like adenovirus or vaccinia virus which could provide transgene expression persistently, are better suited to deliver checkpoint-blocking antibodies (53,86,140). Second, according to the tumor location and individual patient progress, conventional cancer treatments, including chemotherapy and radiotherapy, could be included in the OV-combined tumor immunotherapy to enhance synergistic effects of anti-tumor immune activation (141)(142)(143).…”
Section: Future Directions For Ov-combined Personalized Cancer Immunomentioning
confidence: 99%
“…For example, genetically simple and pro-inflammatory viruses, such as rhabdoviruses, are suitable for cancer vaccine combinations due to the rapid dissemination of such viruses in secondary lymphoid organ and the TME. Conversely, more complex and slower-replicating viruses, like adenovirus or vaccinia virus which could provide transgene expression persistently, are better suited to deliver checkpoint-blocking antibodies (53,86,140). Second, according to the tumor location and individual patient progress, conventional cancer treatments, including chemotherapy and radiotherapy, could be included in the OV-combined tumor immunotherapy to enhance synergistic effects of anti-tumor immune activation (141)(142)(143).…”
Section: Future Directions For Ov-combined Personalized Cancer Immunomentioning
confidence: 99%
“…[77][78][79] It is of course unknown whether, and to what extent, post-exposure prophylaxis prevented the development of EVD, but albeit that these case reports are anecdotal in nature, they are encouraging and provide the basis for current EVD post-exposure recommendations. 76 Vector-specific immunity Although pre-existing anti-VSV immunity is rarely found in humans, 8 anti-vector immunity after vaccination with a VSV vector vaccine might impair vaccine efficacy of future VSV-based vaccines and prime-boost regimens. While data investigating preexisting immunity remain scarce, we recently demonstrated that vaccination with VSV-EBOV induced both vector-specific humoral and cellular immune responses.…”
Section: Correlates Of Protection and Duration Of Immune Responsesmentioning
confidence: 99%
“…7 During the last decade, the recombinant VSV (rVSV) platform has been tested for multiple emerging and neglected viral diseases as well as for therapeutic cancer vaccines in animal studies. 8 Based on the successful establishment of a method to generate VSV from DNA by Rose et al, effective VSV cloning strategies have been implemented 9 and multiple studies revealed the capacity of VSV to express foreign antigens and thus its potential to be used as vaccine candidates. [10][11][12][13] Benefits of the rVSV platform include (reviewed in 14,15 ):…”
Section: Introductionmentioning
confidence: 99%
“…Systemic treatment with oncolytic viruses (OVs) is a promising approach to treat disseminated tumors in different cancer types (1). Vesicular stomatitis virus (VSV), an oncolytic virus of the Rhabdoviridae family, has been demonstrated to be an effective oncolytic agent and vaccine vector platform in clinical trials and animal models (2, 3). However, VSV easily induces a vector-neutralizing antibody response within a few days following administration (4).…”
Section: Introductionmentioning
confidence: 99%